Microsoft Teams : step by step - McFedries, Paul (Pearson Education, 2023)
The quick way to learn Microsoft Teams! This is learning made easy. Get more done quickly with Microsoft Teams in any environment, and help your whole team succeed with it. Jump in wherever you need answersbrisk lessons and detailed screenshots show you exactly what to do, step by step. Build your own teams to enhance collaboration Use team channels to bring structure and relevance to your work Work smarter with apps, tabs, extensions, connectors, and bots Create, upload, edit, and share Microsoft 365 documents inside Teams Stay connected via chat and video calls Get more done in every Teams meeting Customize Teams to maximize personal and organizational efficiency Look up just the tasks and lessons you need.